"We want this to reach a lot of people" or how knowledge mobilisation underpins participatory social research - Susinos, Teresa; Saiz-Linares, Ángela; Ruiz-López, Julia (Education Policy Analysis Archives, 2022)
This work is part of an R+D+i project funded by the Spanish Ministry of Economy and Competitiveness whose purpose is the study of several participatory projects aimed at promoting the participation of socially vulnerable groups. Here we deal with one of these projects where the collaborative creation of an audiovisual2 production was the nucleus of a complex research process on the reality of prison. The participants and co-creators of this work were six young inmates, a social worker and three researchers from the University of Cantabria. We examine how this participatory research intersects with the fundamentals of knowledge mobilisation and how this is revealed throughout the project (not only in the final dissemination) through four interpretative axes: relevance; participatory research, training and social change; accessible, understandable and audience-oriented communication; and active audience allied with the purpose of social transformation. This paper shows how these results emerging from a concrete project can be inspiring for other research projects guided by the paradigm of participation and social action.